Implementation of Child Abuse Act (RA 7610) in Manila: Inputs for Policy Advocacy - Monterona, Marlene M. (JPAIR Multidisciplinary Research, 2016)
The situation of child abuse, exploitation, and discrimination in Asia remain severe, and the extent of the problem in the Philippines is alarming. The study was conducted to assess the implementation of Child Abuse Act (RA 7610) in Manila as a basis for policy advocacy. The researcher used the descriptive method of research as well as purposive sampling based on the respondents’ involvement in the implementation of RA 7610. The data were gathered utilizing a validated self-constructed questionnaire which was supplemented by interview sessions. Results showed that the implementing rules and regulations of RA 7610 are not totally enforced as assessed by the five groups of respondents composed of 253 samples. Findings revealed that there is a great need for education to increase public and multi-disciplinary professional as well as parental awareness of child abuse and protection. Legislation of interdisciplinary community collaboration and professional in-service training is very important for the recognition, proper management, and prevention of child abuse and neglect. A proposed intervention scheme was offered to help in empowering communities and local partners to strengthen the protection of children from abuse, neglect, exploitation and other forms of violence to improve their well-being and fulfill their rights to protection.